Ontogenetic development of the sagittal otoliths of Lipophrys pholis (Blenniidae) during the embryonic, larval and settlement stages - Carvalho, Margarida Gama
Eggs and settlers of Lipophrys pholis were collected during low tides from a northern Portuguese rocky beach in March and May of 2013. The eggs were reared under controlled-laboratory conditions until the larval stage, while settlers were immediately sacrificed. Sagittae were viewed by scanning electron microscopy to assess the occurrence of different microstructural checks during embryonic, larval and settlement stages. Otoliths recorded several micro-increments (8–10) before hatching in late embryo phases. In larval otoliths a visible hatching check was observed and micro-increments were deposited on a daily basis. Early settlers presented in the otolith edge two types of settlement marks. These findings are important to prevent a misidentification of some life history events and/or to avoid overestimation of individual age from otolith studies.